Land Asset Management Of The Indonesian National Army Air Force Education And Training Doctrine Guidance Command To Improve Non-Tax State Revenue Case Study Of Sulaiman Air Force Base - Setiohadi, Tri; Marsono, Marsono; Kemalsyah, Kemalsyah (CV RIFAINSTITUT, 2025)
The Air Force Doctrine, Education, and Training Development Command holds responsibility for air operations and personnel training, as well as managing the land assets under its control. One of the air bases is Sulaiman Air Force Base. In managing land assets, several challenges are encountered, particularly in terms of how the land assets are utilized, safeguarded, and optimized to provide greater benefits, especially in increasing Non-Tax State Revenue (PNBP). The purpose of this study is to review the management of land assets at Sulaiman Air Force Base and identify the improvements needed to maximize their utilization, security, and contribution to Non-Tax State Revenue. This research employs a qualitative method with a descriptive design, and data collection is carried out using strategies to assess how the land assets can be optimized for Non-Tax State Revenue. The study finds that the management of land assets at Sulaiman Air Force Base is still not optimal, with several key issues identified: the current condition of land asset utilization, challenges in land asset management, the potential of underutilized land assets, and strategies for optimization to enhance Non-Tax State Revenue. A comprehensive strategy is needed, including detailed asset inventory and verification, resolution of legal issues, partnerships with third parties, and continuous monitoring and supervision to ensure proper management of land assets at Sulaiman Air Force Base.